Batch sorption and spectroscopic speciation studies of neptunium uptake by montmorillonite and corundum. (1st February 2017) - Elo, O.; Müller, K.; Ikeda-Ohno, A.; Bok, F.; Scheinost, A.C.; Hölttä, P.; Huittinen, N.
Abstract: Detailed information on neptunium(V) speciation on montmorillonite and corundum surfaces was obtained by batch sorption and desorption studies combined with surface complexation modelling using the Diffuse Double-Layer (DDL) model, in situ time-resolved Attenuated Total Reflection Fourier-Transform Infrared (ATR FT-IR) and X-ray absorption (XAS) spectroscopies. The pH-dependent batch sorption studies and the spectroscopic investigations were conducted under carbonate-free conditions in 10 mM NaClO4 or 10 mM NaCl. Solid concentrations of 0.5 g/l and 5 g/l were used depending on the experiment. The neptunium(V) desorption from the two mineral surfaces was investigated at pH values ranging from 8 to 10, using the replenishment technique. Neptunium(V) was found to desorb from the mineral surface, however, the extent of desorption was dependent on the solution pH. The desorption of neptunium(V) was confirmed in the ATR FT-IR spectroscopic studies at pH 10, where all of the identified inner-sphere complexed neptunium(V), characterized by a vibrational band at 790 cm −1, was desorbed from both mineral surfaces upon flushing the mineral films with a blank electrolyte solution. In XAS investigations of neptunium(V) uptake by corundum, the obtained structural parameters confirm the formation of an inner-sphere complex adsorbed on the surface in a bidentate fashion. As the inner-sphere complexes found in the IR-studies are characterized by identical sorption bands on both corundum and montmorillonite, we tentatively assigned the neptunium(V) inner-sphere complex on montmorillonite to the same bidentate complex found on corundum in the XAS investigations. Finally, the obtained batch sorption and spectroscopic results were modelled with surface complexation modelling to explain the neptunium(V) speciation on montmorillonite over the entire investigated pH range. The modelling results show that cation exchange in the interlayer space as well as two pH-dependent surface complexes are required to fully explain the neptunium(V) speciation on the montmorillonite surface.